Influence of Autocorrelated Rhythmic Auditory Stimulations on Parkinson’s Disease Gait Variability: Comparison With Other Auditory Rhythm Variabilities and Perspectives - Lheureux, Alexis; Warlop, Thibault; Cambier, Charline; Chemin, Baptiste; Stoquart, Gaëtan; Detrembleur, Christine; Lejeune, Thierry (Frontiers in Physiology, 2020)
Parkinson’s Disease patients suffer from gait impairments such as reduced gait speed, shortened step length and deterioration of the temporal organization of stride duration variability (i.e. breakdown in Long-Range Autocorrelations). The aim of this study was to compare the effects on Parkinson’s Disease patients’ gait of three Rhythmic Auditory Stimulations (RAS), each structured with a different rhythm variability (isochronous, random and autocorrelated). Nine Parkinson’s Disease patients performed four walking conditions of 10-15 minutes each: Control Condition (CC), Isochronous RAS (IRAS), Random RAS (RRAS) and Autocorrelated RAS (ARAS). Accelerometers were used to assess gait speed, cadence, step length, temporal organization (i.e. Long-Range Autocorrelations computation) and magnitude (i.e. coefficient of variation) of stride duration variability on 512 gait cycles. Long-Range Autocorrelations were assessed using the evenly spaced averaged Detrended Fluctuation Analysis (α-DFA exponent). Spatiotemporal gait parameters and coefficient of variation were not modified by the RAS. Long-Range Autocorrelations were present in all patients during CC and ARAS although all RAS conditions altered them. The α-DFA exponents were significantly lower during IRAS and RRAS than during CC, exhibiting anti-correlations during IRAS in 7 patients. α-DFA during ARAS was the closest to the α-DFA during CC and within normative data of healthy subjects. In conclusion, Isochronous RAS modify patients’ Long-Range Autocorrelations and the use of Autocorrelated RAS allows to maintain an acceptable level of Long-Range Autocorrelations for Parkinson’s Disease patients’ gait.